The reproductive performance of the Mupli beetle, Luprops tristis , in relation to leaf age of the para rubber tree, Hevea brasiliensis - Sabu, T. K. (Oxford University Press, 2014)
An analysis of host plant leaf age preferences and phenology studies led to the predictions that tender rubber plant leaves are essential for the completion of the life cycle of the Mupli beetle, Luprops tristis Fabricius (Coleoptera: Tenebrionidae) and that low tender leaf availability during the post-dormancy stage will limit the beetle population. Analyses of the effects of feeding the beetles leaves of various ages, nitrogen (N) content, and moisture content on fecundity and the duration of post-dormancy survival were carried out. The results showed that tender leaf availability during the post-dormancy phase of L. tristis is a critical factor that determines the survival of L. tristis adults and the subsequent generation. The control of powdery mildew ( Odium hevea ) disease-mediated premature leaf fall in rubber plantations may regulate the beetle population. A peak in fecundity during the early phase of post-dormancy is proposed as an adaptive mechanism of L. tristis to synchronize egg production and feeding with tender leaf availability in rubber plantations. Variations in nutrient levels and moisture content between deciduous rubber tree leaves of different ages are attributed to the leaf nutrient resorption mechanism of senescing leaves. These results established that tender leaves with high N and moisture levels are essential for post-dormancy survival and that N influences fecundity. The results of the experiments could aid decision making regarding the population management and control of L. tristis in rubber plantations.